An stiffness coefficients proposal for thin walled open beams - Ruiz Sibaja, Alejandro; Bonilla Manterola, Oscar (Rev. Téc. Fac. Ing. Univ. Zulia, 2010)
According to the conventional formulation it is considered that the warping of a beam under torsion is free and constant among a section and the other. This consideration is unacceptable for thin walled open elements since has been shown that in these the warping is variable and originates a different state of stress of which that considers the traditional approach. Therefore, it is necessary to include these effects when it analyses restricted torsion in this structural type of elements. This paper shows a method to obtain stiffnes coefficients in thin walled open beams by using the differential equations and the matrix of initial parameters presented by V. Z. Vlasov. Some initial results are presented obtained with the model proposed.